2011
DOI: 10.1016/j.pec.2010.01.021
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of communication training with primary care providers to improve patient-centeredness and health risk communication

Abstract: Objective To determine the efficacy and effectiveness of training to improve primary care providers’ patient-centered communication skills and proficiency in discussing their patients’ health risks. Methods Twenty-eight primary care providers participated in a baseline simulated-patient interaction and were subsequently randomized into intervention and control groups. Intervention providers participated in training focused on patient-centered communication about behavioral risk factors. Immediate efficacy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(100 citation statements)
references
References 45 publications
0
92
1
2
Order By: Relevance
“…31 Shared decision making can be considered as a component of patientcentred communication, and while there is some overlap between the skills that are taught and evaluated in trials of patient-centred communication training and our study, there are also some differences. Most notably, our intervention also emphasised the incorporation of evidence into the decision making process, including presentation of the probability (or likely size) of the benefits and harms of each option being discussed and the associated strategies for presenting this numerical information in a manner that patients can understand.…”
Section: Discussionmentioning
confidence: 74%
“…31 Shared decision making can be considered as a component of patientcentred communication, and while there is some overlap between the skills that are taught and evaluated in trials of patient-centred communication training and our study, there are also some differences. Most notably, our intervention also emphasised the incorporation of evidence into the decision making process, including presentation of the probability (or likely size) of the benefits and harms of each option being discussed and the associated strategies for presenting this numerical information in a manner that patients can understand.…”
Section: Discussionmentioning
confidence: 74%
“…Lifestyle changes or non-pharmacological treatment (smoking cessation, reducing alcohol intake, weight reduction, diet, physical activity and stress management) and pharmacological treatment have been found, on the basis of extensive research, to be important in reducing the risk of cardiovascular complications [5,6]. The growing knowledge of behavioural models for changing lifestyle and increasing adherence is unfortunately seldom taken into account [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…[48][49][50] Early studies of such interventions have demonstrated benefits in both better communication and increased access to and use of health care. [51][52][53][54] The concept of the patient-centered medical home has gained widespread support over the past decade. Our study supports the call to better define patient-centered medical homes and evaluate the model in different settings to determine its effects on improving quality and reducing inequities in care.…”
Section: Discussionmentioning
confidence: 99%